Development and Description of a New Multifidus‐Sparing Radiofrequency Neurotomy Technique for Facet Joint Pain. Issue 7 (13th April 2021) - Russo, Marc A.; Santarelli, Danielle M.
Abstract: Introduction: The technique of radiofrequency neurotomy (RFN) of the facet joints has been used for decades to treat persistent low back pain to good effect in carefully selected patients. Traditionally, the target is the medial branches of the dorsal root supplying the facet joint. An alternative denervation target is the facet joint capsule. Capsule‐targeting techniques may spare the multifidus muscle, a possible unintended target of traditional RFN that is thought to be important in recovering from low back pain, and have shown promising results. Methods: A modified RFN technique that targets the capsule and spares the multifidus (multifidus‐sparing RFN) is described here, along with a brief report of its application in patients with symptomatic facet joint low back pain as compared to traditional medial branch RFN (MBRF). Results: Over a 2‐year period, a total of 401 initial multifidus‐sparing RFN and 94 initial MBRF procedures were performed on patients attending a multidisciplinary pain clinic. The proportion of repeat procedures was similar: 28.4% of multifidus‐sparing procedures and 23.4% of MBRF procedures. The median repeat interval was 12 months for both groups and interquartile range was 10 months (8–18 months) for multifidus‐sparing RFN and 4 months (11–15 months) for MBRF. Effectiveness and safety profiles appear to be similar, although limited, retrospective outcome information prevented robust analysis. Conclusion: Multifidus‐sparing RFN represents an intriguing technique to denervate the facet joint pain generator while maintaining normal multifidus function. Further study is warranted, particularly in order to identify the appropriate patient criteria and long‐term outcomes.